2019
DOI: 10.3341/kjo.2019.0031
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Slanted Recession of Bilateral Lateral Rectus Muscle for Intermittent Exotropia with Convergence Insufficiency

Abstract: Purpose To evaluate the long-term efficacy of slanted lateral rectus recession in children for reducing distance and near exodeviation and near-distance deviation difference in intermittent exotropia with convergence insufficiency. Methods The medical records of 53 patients with convergence insufficiency intermittent exotropia who underwent slanted bilateral lateral rectus recession performed by a single surgeon and received follow-up for more than 12 months were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
1
10
5
Order By: Relevance
“…It was reported that this procedure was superior in reducing both distance and near deviations and in reducing the distance-near deviation difference. In two other studies performed by Kwon et al [14] and Farid et al [15], this procedure was also proved to be safe and efficient in reducing the distance and near deviation and also the distance-near difference of deviation. However, further studies are still needed.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…It was reported that this procedure was superior in reducing both distance and near deviations and in reducing the distance-near deviation difference. In two other studies performed by Kwon et al [14] and Farid et al [15], this procedure was also proved to be safe and efficient in reducing the distance and near deviation and also the distance-near difference of deviation. However, further studies are still needed.…”
Section: Introductionmentioning
confidence: 74%
“…At 6 months postoperatively, none of the children demonstrated abduction limitation, diplopia, consecutive esotropia, torsion, or A-V pattern misalignment. In Kwon and Lee's study[14], 53 patients with CI-IXT underwent SLR-rec with a follow-up of more than 12 months. At the last follow up, surgical success rate was 58.5%, and a distance-near deviation difference ≤ 8 PD was measured in 81.1% of patients, which also confirmed the efficiency of SBLR in reducing the distancenear deviation difference.…”
mentioning
confidence: 99%
“…In another study including 31 children with CI-IXT conducted by Chun and Kang [2], the success rate was reported to be 83.9%. And in Kwon and Lee's study [14] in which 53 patients with CI-IXT underwent SBLR-rec with a follow-up of more than 12 months, the surgical success rate was 58.5%. Farid and Abdelbaset [15] compared the three surgical procedures for treatment of CI-IXT, which were, slanted bilateral LR recession(S-BLR), the improved unilateral MR resection-LR recession in which the resection were based on the near deviation and the recession on distance deviation, and augmented bilateral LR recession (A-BLR) in which the recession was based on the near deviation.…”
Section: Discussionmentioning
confidence: 92%
“…However, Farid and Abdelbaset [15] compared SBLR-rec with two other surgical procedures and reported no significant differences among the three groups in the success rates of distance exodeviation, near exodeviation, and N-D deviation difference after 1 year. Moreover, they reported cases of asymptomatic vertical pattern strabismus after SBLR-rec procedure, while the other studies [1,2,14] didn't report similar findings. In the present study, we retrospectively analyzed the surgical results of 34 patients who underwent SBLR-rec for CI-IXT with a minimum follow-up of 6 months.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation